Escherichia coli-mycobacteria shuttle vectors for operon and gene fusions to lacZ: the pJEM series. - Timm, J (1994)
A series of Escherichia coli-mycobacteria shuttle plasmids for the isolation and study of gene regulatory sequences was constructed. These pJEM vectors contain an efficient transcription terminator and multiple cloning sites and allow either operon or gene fusions to lacZ. By constructing operon fusions with pJEM15, we assessed various previously characterized mycobacterial promoters in the fast-growing species Mycobacterium smegmatis and the slow-growing species M. bovis BCG. Our results suggest that M. smegmatis and M. bovis BCG RNA polymerases do not share the same specificity. To isolate new mycobacterial promoters, an M. tuberculosis DNA library was generated, using pJEM13, and screened in M. smegmatis. Several Lac+ clones were isolated, and the beta-galactosidase activity was measured.